A Study of Casual Relationship of Job Design and Employee’s Behavior - Muneer, Saqib; Jamil, Khalid; Idrees, Muhammad (Information Management and Business Review, 2018)
Some factors other than higher salaries, compensation benefits and conducive workplace seem to have strong impact on employee’s performance i.e. organization citizenship behavior and counterproductive work behavior. Purpose of this study is to examine the impact of job design elements i.e. job enlargement, job enrichment and job rotation on employee’s organizational citizenship behavior and counterproductive work behavior in the banking sector of Faisalabad and extent to which this relationship is mediated by motivation. Data was collected from 170 frontline managers of banks. After analysis of data, it was found that that there is a positive and significant relationship between job enlargements, job enrichment on OCB while negative and significant relationship between job rotation and OCB. Negative and significant relationship between job enlargement and CWB, negative but insignificant relationship between job enrichment and CWB while positive and significant relationship was found between the job rotation and CWB. Motivation was partially mediating the relationship between job enlargement, enrichment, rotation and organizational citizenship behavior, while motivation was partially mediating the relationship between job rotation and counterproductive work behavior. This study enhances the existing literature of job design and contributes to research by finding how job design influences the OCB & CWB.